Interactive relighting with dynamic reflectance - Zhou, Kun; Chen, Yanyun; Lin, Steve; Guo, Baining (2011)
Interactive relighting with dynamic reflectance involves relighting a graphical scene with dynamic changes to the reflectance(s) in the graphical scene. A graphical scene may include source radiance, regions having reflectances, a surface spot, incident radiation from the source radiance at the surface sport, an incident direction, a viewing direction, exit radiance, and so forth. In an example embodiment, a graphical scene is relighted based on at least one adjusted reflectance of the graphical scene using an incident radiance at a surface spot that is separated into respective incident radiance components corresponding to different respective numbers of interreflections in the graphical scene. In another example embodiment, a graphical scene is relighted based on at least one adjusted reflectance of the graphical scene using a tensor representation for a reflectance of a surface spot with the tensor representation being segmented into three adjustable factors for lighting, viewing, and reflectance.
US Patent 7884820 B2